The Issue of Effective Leadership in Political Science - Doncheva, Hristina (Research Papers, 2012)
Effective leadership requires purposeful, persistent and hard work of the leader and their followers to achieve the objectives of the community. Political leadership is a process which results can be objectively assessed only after a certain time – in the indefi nite future. It - leadership effectiveness is something far more complex than the sum of any results and is diffi cult to be defi ned precisely.The study analyzes in a sequel: the close interdependence of questions about the nature and effectiveness of the leadership phenomenon, the interrelations leadership – power – authority and leadership – political change; the reasons for the lack of consistence in the leadership theory in a conceptual manner and others. It is suggested to enrich the theoretical framework for the study of leadership with three additional concepts: the subject of human activity, consciousness and personality.In the last two parts of the study the dominant theoretical literature on effective leadership are presented and subjected to critical analysis, particularly the criteria for effectiveness. Special attention is paid to the issue of distinguishing the concepts of "leadership effectiveness" and "effective leadership". Indicators for manifestation of effective political leadership are derived.